Romania And The British Model Of Government (1866-1914) : A New Approach To The Study Of The Romanian Politics - Cosmin-Stefan, Dogaru (European Scientific Journal, ESJ, 2016)
In 1866, following the accession of a foreign prince to the Romanian throne and the sanctioning of the new Constitution, the Romanian political elite managed to strengthen the political regime of the age. Both conservative and liberal leaders became conscious of the necessity of structuring a political regime based on the constitutional monarchy, which could generate political, cultural and social-economic changes. The liberal and conservative politicians, many of which were educated abroad, imposed a series of new principles, ideas and values in the Romanian realm in the second half of the 19th century. These invariably lead to a gradual change of the political regime, the political elite wanting and managing to diminish the gap between Romania and the other European states to a great extent. The present article proposes a new perspective, based on historical facts studied with the instruments of political science and addressing a topic that belongs to the political history and that calls the attention of numerous scholars nowadays. I also intend to discuss a new approach regarding the analysis of an important aspect of the Romanian political regime. My research concentrates on the following research challenge: How was the British classical model adjusted to the Romanian realm and how did it generate a two-party system with specific features for the Romanian political life?